Modern Technologies to Improve Energy Efficiency - Elbekovna, Umarova Nazira; Rustamovna, Nurmukhamedova Diera; Mamurova, F. I. (European Journal of Life Safety and Stability (2660-9630), 2023)
Houses built before the 2000s cannot meet today's high energy efficiency requirements. At the time of their construction, there were completely different standards, and technology did not allow for a serious reduction in heat loss. Today, developers have a whole arsenal of knowledge, materials and technologies that will allow them to build an energy-efficient apartment building.